2016
DOI: 10.1089/thy.2016.0060
|View full text |Cite
|
Sign up to set email alerts
|

Adeno Associated Virus 9–Based Gene Therapy Delivers a Functional Monocarboxylate Transporter 8, Improving Thyroid Hormone Availability to the Brain of Mct8-Deficient Mice

Abstract: These results indicate that MCT8 delivery to brain barriers by IV but not ICV injection is crucial for its proper function. MCT8 has no constitutive activity but acts through an increase in T3 entering the brain tissue. Increasing MCT8 expression in brain cell membranes, including neurons, is insufficient to produce an effect without an increase in brain T3 content. The correct hMCT8 isoform along with an optimized delivery method are critical for an effective gene therapy to provide functional MCT8 in the bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…Furthermore the function of MCT8 mutants is also dependent on the cellular context 31 . The only known function of MCT8 is facilitated cellular transport of iodothyronines across the plasma membrane and no other substrates have been described in vertebrates 32 , 33 and a recent study confirmed that MCT8 lacks constitutive activity 34 . We have previously shown that the zebrafish MCT8 knockdown displayed locomotor, cellular and molecular changes congruent with the human neurological symptoms of AHDS 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore the function of MCT8 mutants is also dependent on the cellular context 31 . The only known function of MCT8 is facilitated cellular transport of iodothyronines across the plasma membrane and no other substrates have been described in vertebrates 32 , 33 and a recent study confirmed that MCT8 lacks constitutive activity 34 . We have previously shown that the zebrafish MCT8 knockdown displayed locomotor, cellular and molecular changes congruent with the human neurological symptoms of AHDS 15 .…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that, although Mct8 is also expressed in neurons and glial cells, endothelial-cell-specific expression of Mct8 makes the BBB permeable to TH and enables TH access into the brain, which is sufficient to induce myelination. Recently, intravenous injection of adeno-associated virus 9 driving the expression of human MCT8 was shown to increase T3 content in the mouse brain (Iwayama et al, 2016). Further studies that test the effect of vascular Mct8 expression on neurons and glial cells in various brain regions in mct8 −/− larvae and mouse models are required in order to evaluate this treatment approach.…”
Section: Discussionmentioning
confidence: 99%
“…These barriers tightly control the influx and efflux of molecules and ions at the blood-brain interface to meet neural cell needs and to protect the brain from toxins and pathogens (Obermeier et al, 2013 ). The severe alterations present in MCT8-deficient patients (Fu et al, 2013 ) revealed the relevance of TH transporters and the importance of TH transport across brain barriers (Ceballos et al, 2009 ; Iwayama et al, 2016 ; Vatine et al, 2017 ). Studies in the rat indicated that the contribution of the choroid plexus to the total brain TH content is about 18% (Chanoine et al, 1992 ) and, since the BBB surface area is much greater than that of the choroid plexus, the BBB has been considered the major pathway for TH entry into the brain (Dratman et al, 1991 ).…”
Section: Brain Barriers and Thyroid Hormonesmentioning
confidence: 99%